The Impact Of Service Quality And Price On Customer Satisfaction (Case Study Of Integrated Rail Crossing) - Pratama, Aldiwa; Marcell Aditiya Pratama; Nurliya Apriyana (SEAN Institute, 2024)
This research aims to examine the influence of service quality and price on costumer satisfaction in the Integrated Rail Crossing (LRT) case study. The method used is descriptive quantitative with purposive sampling technique. Primary data was obtained through a questionnaire distributed using Google Form involving 142 LRT user respondents aged 17-55 years. The analysis technique used is partial least squares with the SmartPLS version 4 analysis tool. The research results of service quality (X1) have a positive and significant influence on consumer satisfaction (Y) and price (X2) has a positive and significant influence on consumer satisfaction (Y). The research results show that service quality and price have a significant influence on LRT consumer satisfaction.